2018
DOI: 10.5210/fm.v23i11.8159
|View full text |Cite
|
Sign up to set email alerts
|

Sharing by proxy: Invisible users in the sharing economy

Abstract: With the future of work increasingly data-driven, platforms automate decisions based on the collection of vast quantities of user data. However, non-users constitute a challenge as they provide little to no data for either platforms or other users. We focus on a category of (non-)users that has not received any attention in research: users-by-proxy. Users-by-proxy make use of sharing services but they are not themselves part of the sharing transaction. Platforms cannot analyze their behavior to tailor services… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In other countries, the numbers seem to be higher. In a Pew study (Zickuhr, 2013), 44 percent of Internet non-users in the United States were identified as users-by-proxy; the same proportion is reported in a study about Switzerland with representative data from 2009 (Friemel, 2016). Dolničar, et al (2013) found that over 40 percent of reported non-users had made use of internet intermediaries.…”
Section: Use-by-proxymentioning
confidence: 62%
“…In other countries, the numbers seem to be higher. In a Pew study (Zickuhr, 2013), 44 percent of Internet non-users in the United States were identified as users-by-proxy; the same proportion is reported in a study about Switzerland with representative data from 2009 (Friemel, 2016). Dolničar, et al (2013) found that over 40 percent of reported non-users had made use of internet intermediaries.…”
Section: Use-by-proxymentioning
confidence: 62%
“…According to many authors (e.g., Prendeville et al, 2017;Unterfrauner et al, 2019), the activities of makerspaces are already tangential to many principles of the circular economy, e.g., by extending product life through repair and sharing resources by collaborative commons. In addition, the aspect of education can be perceived as a tentative move toward a general participation in the sharing industry (Newlands et al, 2018). In contrast to engineers concentrating primarily on the specific product properties and functionalities (Halstenberg et al, 2019) and following strictly pre-defined processes, designers develop concepts implemented in the approach of eco or sustainable design (Sherwin, 2004) to improve the environmental performance of products.…”
Section: Scientific Starting Points: Makerspaces Makers and Behaviora...mentioning
confidence: 99%
“…Beyond this, future research within a digital inequalities paradigm should study the distinction mechanisms and new hierarchies in the digital economy (Schor et al, ), also in terms of new skills such as algorithmic literacy (Klawitter & Hargittai, ). The research should not only systematically assess who is earning money as a freelancer or provider on digital platforms such as Airbnb and Uber but also who is using on‐demand services as a consumer (Andreotti, Anselmi, Eichhorn, Hoffmann, & Micheli, ; Smith, ) or user‐by‐proxy (Newlands, Lutz, & Hoffmann, ).…”
Section: Second‐level Digital Dividementioning
confidence: 99%